PORTRAYING MATERNAL LOVE DIVERSITY OF SELECTED CHARACTERS IN DUMPLIN’ NOVEL BY JULIE MURPHY (EUFONI: Journal of Language, Literary, and Cultural Studies, 2021)
This study aims to analyze diverse type of maternal love possessed by selected female characters in Dumplin’, a novel by Julie Murphy. Dumplin’ is chosen as object of this study which firstly published in 2015 about a sixteen years old girl who lives with her mother, but she is raised by her aunt. Receiving conditional love from her biological mother causes her possessing obsessive attributes. Besides, she also receives unconditional love from her aunt which causes her experiencing conditional depression. This study uses qualitative approach by identifying the issue and presenting the results in form of text. Using Erich Fromm’s (1956) theory about love, distinct version of maternal love is portrayed and observed through main character’s point of view. The result of this study shows that there are distinctive type of maternal love in form of conditional love of biological mother and unconditional love of non-biological mother which affect main character’s psychology.